Study of The Chemical Properties of The Post-Harvest Peanut (Arachis hypogaea L.) Pertilized by The Mushroom Baglog Waste Compost - Zuhraini Zuhraini; R. Sutriono; Lolita Endang Susilowati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Availability in the soil varies greatly, influenced by the interaction between the chemical properties of the soil and some other soil traits such as the physical and biological properties of the soil. An analysis of the chemical properties of the soil is vital to recognizing availability of nutrients for future crop cultivation. The purpose of this study is to know the chemical conditions of the ground after the harvest of the peanut plant after given the mushroom compost post fertilizer. The design of the experiment used in this study is a complete random design (ral) with a dose of mushroom post baglog fertilizer 6 and a degree of fertilizer recommendation 1 (as control). As for the treating cedar that is used is p1 = 100% recommendation fertilizer, p2 = 2 ton ha-1 fertilizer compost of the mushroom baglog, p4 = 4 tons of ha-1 fertilizer compost of the mushroom baglog, p5 = 6 tons of ha-1 Studies show a different dosage of fertilizer has a real impact on all the parameters observed.